Pengaruh Celebrity Endorsement Terhadap Purchase Intention Dengan Brand Awareness Sebagai Variabel Mediasi: Studi Kasus Pada Konsumen Brand Rucas - Wahyu Pratama, Pradipta Agung; Darma Putra, Muhammad Bintang; Teguh Wicaksono, Firdaus; Indra Parahita, Albertus; Syamsyah Alvaraisa, Revaldy (Faculty of Economic and Business Wijaya Kusuma Surabaya University, 2026)
Indonesia’s local fashion industry has grown rapidly, encouraging local brands such as RUCAS to optimize digital-based marketing communication strategies. One widely used strategy is celebrity endorsement, which is expected to enhance brand awareness and stimulate consumers’ purchase intention. This study aims to analyze the effect of celebrity endorsement on purchase intention, with brand awareness acting as a mediating variable among RUCAS consumers. A quantitative explanatory, cross-sectional design was employed, using a sample of 50 consumers aged 18–35 years in Surabaya who had been exposed to RUCAS celebrity endorsement campaigns. Data were collected through an online questionnaire using a five-point Likert scale and analyzed descriptively and inferentially to test four research hypotheses. The results indicate that celebrity endorsement has a positive and significant effect on both brand awareness and purchase intention, while brand awareness also has a positive and significant effect on purchase intention. Furthermore, brand awareness is found to mediate the relationship between celebrity endorsement and purchase intention, strengthening the impact of celebrity endorsement when consumers possess high awareness of the RUCAS brand. These findings highlight the importance of selecting credible, attractive, and brand- congruent celebrities when designing digital marketing campaigns in the local fashion industry.